A systematic review of trends in research on seabird behavioral flexibility - Biagiotti Barchiese, María Candelaria (2023)
There has been an increase in interest in the study of behavioral flexibility for its role in how organisms face disturbances and changes in their environment. However, there is not much research on this topic for seabirds, whose conservation status is affected by multiple issues related to changes in their environment. The goal of this paper was to analyze research on seabird behavioral flexibility and to identify knowledge gaps. A systematic review was conducted using academic search engines and including articles published from 1986 to 2022. In the 143 articles that were analyzed, the following were identified: publication date, family and species being studied, annual cycle period, research context and focus, behavioral flexibility components studied, and related environmental issues. The results show that the study of the issue in seabirds increased between 1986 and 2022, especially for the Spheniscidae, Alcidae, and Laridae families. Most studies were conducted in the field during the reproductive period in a parental-care context, mainly focusing on behavioral diversity and personality. In the studies that focused on behavioral flexibility mechanisms, the most-studied components were neophobia and exploration, whereas in the mixed-approach studies, the study of boldness prevailed. The environmental issue that was examined the most was global climate change. Our review shows that, even if the number of studies on seabird behavioral flexibility has increased in the last decade, few of them focus on the links between specific behavioral flexibility components, conservation status, and the environmental issues pertaining to the places where the species live.